Hemodynamic Profiles Before and After Surgery in Bicuspid Aortic Valve Disease—A Systematic Review of the Literature - Cave, Daniel G. W.; Panayiotou, Hannah; Bissell, Malenka M. (Frontiers in Cardiovascular Medicine, 2021)
Bicuspid aortic valve (BAV) disease presents a unique management challenge both pre- and post-operatively. 4D flow MRI offers multiple tools for the assessment of the thoracic aorta in aortic valve disease. In particular, its assessment of flow patterns and wall shear stress have led to new understandings around the mechanisms of aneurysm development in BAV disease. Novel parameters have now been developed that have the potential to predict pathological aortic dilatation and may help to risk stratify BAV patients in future. This systematic review analyses the current 4D flow MRI literature after aortic valve and/or ascending aortic replacement in bicuspid aortic valve disease. 4D flow MRI has also identified distinct challenges posed by this cohort at the time of valve replacement compared to standard management of tri-leaflet disorders, and may help tailor the type and timing of replacement. Eccentric pathological flow patterns seen after bioprosthetic valve implantation, but not with mechanical prostheses, might be an important future consideration in intervention planning. 4D flow MRI also has promising potential in supporting the development of artificial valve prostheses and aortic conduits with more physiological flow patterns.